Bahasa Inggris - Putri Ayu Salsabila; Della Ainurrohma; Indah Wahyuningtyas (Program Studi Teknik Kimia Universitas Jember, 2024)
The depletion of fossil fuels has now occurred in various parts of the world. Meanwhile, the demand for fuel energy continues to increase. This condition encourages researchers to look for alternative fuels with high availability of raw materials. Bioethanol is an environmentally friendly renewable energy with biomass production raw materials, it can be an alternative solution to replace fuel oil. One of the biomass that has the potential to be used as a raw material for bioethanol production is tobacco. Tobacco stems have high cellulose and hemicellulose content so that they can be used in bioethanol production. This research method uses base pretreatment and base hydrolyzate, then fermentation and distillation processes are carried out. The results of tobacco stem bioethanol were analyzed using the Response Surface Methodology (RSM) approach, Central Composite Design (CCD) model. During the fermentation process, three independent variables were used, namely the fermentation time of 72-168 hours, pH 4-5, and starter concentration of 0.1% - 0.3%. The results of the Analysis of Variance (ANOVA) of ethanol content showed that the significant variables were the fermentation time and starter concentration. The results of the CCD analysis were obtained at optimum time conditions of 120 hours, pH 4.5 and starter concentration of 0.2% with a bioethanol content of 23.007%.